Functional Significance of Central D1 Receptors in Cognition: Beyond Working Memory - Takahashi, Hidehiko; Yamada, Makiko; Suhara, Tetsuya (Journal of cerebral blood flow and metabolism, 2012)
The role of dopamine D1 receptors in prefrontal cortex function, including working memory, is well acknowledged. However, relatively little is known about their role in other cognitive or emotional functions. We measured both D1 and D2 receptors in the brain using positron emission tomography in healthy subjects, with the aim of elucidating how regional D1 and D2 receptors are differentially involved in cognitive and emotional functions beyond working memory. We found an inverted U-shaped relation between prefrontal D1 receptor availability and Wisconsin Card Sorting Test performance, indicating that too little or too much D1 receptor stimulation impairs working memory or set shifting. In addition, variability of D1 receptor availability in the amygdala and striatum was related to individual differences in emotional responses and decision-making processes, respectively. These observations suggest that the variability of available D1 receptors might be associated with individual differences in brain functions that require phasic dopamine release. An interdisciplinary approach combining molecular imaging of dopamine neurotransmission with cognitive neuroscience and clinical psychiatry will provide new perspectives for understanding the neurobiology of neuropsychiatric disorders such as schizophrenia, addiction and Parkinson's disease, as well as novel therapeutics for cognitive impairments observed in them.